Penerapan Etika Bisnis Dalam Perjanjian Kerja Konstruksi Pada Proyek New Oncology PT. Fahrenheit Di Kabupaten Tangerang - Sulasno Sulasno; Hasuri Hasuri; Devi Junia Fitri (JURNAL HAK : Kajian Ilmu Hukum, Administrasi Negara, dan Komunikasi, 2024)
A value contained in ethics must be a reference, goal and guide in acting and behaving that will bring positive consequences and influences morally. The practice of ethical violations in implementing the New Oncology project occurs in the form of dishonesty and weak integrity in implementing an agreement. The agreement must contain everything that has been mutually agreed upon so that a consensus agreement on the agreement is a valid (legal) agreement for both parties. party. This research aims to find out about the application of business ethics in construction work agreements and aims to find out the form of dispute resolution in construction work agreements on the New Oncology project regarding delays in work completion times at PT. Fahrenheit in Tangerang Regency. This study uses a qualitative method with empirical juridical approaches. The data used are primary and secondary data. The results of this research: 1. The application of business ethics in the construction work agreement on the New Oncology project is in accordance with the agreement but in practice there are defaults; 2. Settlement of legal disputes in this agreement is carried out by means of non-litigation, if a solution cannot be found in this method, it will be resolved by means of litigation. Keywords: Application of Ethics, Agreement, Default, Dispute Resolution